Filling Material Bond Strength to Dentin Is Positively Influenced by the Agitation of Endodontic Final Irrigating Solutions - Aparecida da Silva Trandafilov, Alessandra; Grazziotin-Soares , Renata; Arruda Nogueira, Amanda Palmeira; Matos Maia-Filho, Etevaldo; Coelho Ferreira, Meire; Rodolfo de Jesus Tavarez, Rudys; Bauer, José; Nunes Carvalho, Ceci (Iranian Endodontic Journal, 2024)
Introduction: The final step of irrigation has been considered to of increase the bonding strength of filling material to dentin. This study investigated the impact of three final-step irrigation methods on the endodontic sealer bond strength to dentin by using a micro push-out test. Materials and Methods: Palatal roots of human maxillary molars were cleaned and shaped and randomly divided in six groups (n=15) according to the final-step irrigation method and the type of root canal sealer used. The solutions used for the final-step irrigation were 17% ethylenediaminetetraacetic acid and 2.5% sodium hypochlorite, which underwent three methods: 1) syringe-needle irrigation/conventional, 2) passive ultrasonic irrigation, and 3) XP-endo Finisher agitation. The root canal sealers used were: EndoSequence BC Sealer, and AH-Plus sealer. Roots were obturated with the single cone technique and then, cross-sectioned in 2-mm-thick slices (3 slices from each root). Push-out test was performed on the sliced specimens (cervical, middle, and apical thirds) with a universal testing machine. Bond strength values were recorded in megapascal (MPa). Subsequently, each specimen was longitudinally split to verify the type of failure. Data analysis was performed using Johnson transformation, three-way analysis of variance, Tukey’s post-hoc tests, and the partial Eta squared test. Results: There were significant differences in bond strength between the sealers [AH: 4.46±2.24 and BC: 3.47±2.19 MPa (P<0.001)]; between final-step irrigation methods [passive ultrasonic irrigation: 4.52±2.25, XP-endo Finisher: 3.93±3.93 and syringe-needle irrigation/conventional: 3.37±2.51 MPa (P<0.001)], and between the root canal thirds represented by the sliced specimens [cervical: 5.45±2.39, middle: 4.14±1.99 and apical: 2.30±1.30 MPa (P<0.001)]. The interaction between the variables had no significance (P>0.05). Conclusion: Agitation of the final irrigating solution may improve the bonding of the sealer to canal walls. AH-Plus sealer had the highest bond strength. The bond strength reduced significantly towards the apical third.